Physicochemical Analysis of Nephelium Lappaceum Seed Fat and its Application in Topical Formulations - Gouri Kumar Dash (Journal of Global Pharma Technology, 2019)
Nephelium lappaceum L. (Family- Sapindaceae), popularly known as ‘Rambutan’, is well known for its edible fruits with delicious taste and flavour in Southeast Asia. The fruits are deseeded during processing in the canning industry and considered as a waste by-product. The seeds contain good amount of fatty material and has been claimed to be a source of natural edible fat. The objective of the study was to report the physicochemical parameters of the seed fat together with formulation of few topical preparations such as creams and lotions containing the seed fat that would offer new prototype formulations containing natural ingredients. The physicochemical analysis of the seed fat such as melting point, saponification value, acid value, ester value and peroxide value were studied. The GC-MS analysis of the seed fat was carried out to find its chemical composition. Further, two topical preparations such as creams and lotions were prepared using the seed fat and evaluated using standard recommended procedures. The seed fat was compatible to be used as an ingredient in the bases of creams or lotions. Keywords: N. lappaceum seed fat, Physicochemical analysis, GC-MS analysis, Topical formulations